Synthesis and functional properties of (Al0.2Co0.2Fe0.2Ni0.2Ti0.2)3O4 high entropy spinel oxide - Mishra, Rajesh K. [UNESP]; Minussi, F. B. [UNESP]; Kumari, Priyanka; Shahi, Rohit R.; Araújo, E. B. [UNESP] (Elsevier, 2024)
The present study reports the synthesis of a novel (Al0·2Co0·2Fe0·2Ni0·2Ti0.2)3O4 high entropy oxide (HEO) through the solid-state reaction method and its structural, dielectric, electric, and magnetic properties. For the first time, a cumulative study of dielectric, electric, and magnetic properties of the spinel HEO has been investigated in detail. The obtained HEO has a single-phase spinel structure with Fd-3m space group, confirmed through X-ray diffraction and Raman spectroscopy techniques. Moreover, Raman spectroscopic analysis also confirms that the synthesized spinel HEO is an inverse spinel. The dielectric and magnetic characterizations reveal a better dielectric permittivity of ε′=35 at 1 MHz and high saturation magnetization Ms = 8.58 emu/g with low magnetic coercivity. The leakage current characteristics studied in terms of J-E curves indicate an ohmic conduction mechanism at a low electric field. Moreover, the high dielectric permittivity with resistive switching behavior (observed in the J-E curve) indicates its potential application in resistive switching memory devices, which have better functionality and enhanced scalability.
Keywords: Dielectric and magnetic behavior; High entropy oxide; Raman spectroscopy; RS behavior; Spinel structure